The Effect of Antiviral Therapy on Liver Fibrosis Regression in Chronic Hepatitis B and C: A Comprehensive Review - Shavkat o`g`li, Kurbonov Khayitjon (American Journal of Biomedicine and Pharmacy, 2025)
Antiviral therapy (AVT) has revolutionized the management of chronic hepatitis B (CHB) and chronic hepatitis C (CHC), transforming the disease course and prognosis for millions worldwide. A critical aspect of this therapeutic success is the documented potential for liver fibrosis regression following viral suppression or eradication. This comprehensive review synthesizes the existing literature on the impact of modern AVT on fibrosis regression in both CHB and CHC, highlighting the distinct mechanisms and outcomes associated with different treatment modalities. The review focuses on oral nucleos(t)ide analogues (NAs) for CHB, particularly entecavir (ETV) and tenofovir (TDF), and direct-acting antivirals (DAAs) for CHC. We examine the roles of invasive (liver biopsy) and non-invasive markers (e.g., transient elastography [TE], FIB-4, APRI) in monitoring fibrosis dynamics. Key findings indicate that AVT significantly reverses liver fibrosis in both conditions, with viral eradication in CHC often leading to more profound and rapid regression. However, long-term monitoring for hepatocellular carcinoma (HCC) and other liver-related complications remains essential, especially in patients with advanced fibrosis at baseline.